Theoretical investigation of acoustic wave velocity of aluminum phosphide under pressure - Daoud, Salah; Latreche, Abdelhakim; Kumar Saini, Pawan (International Journal of Physical Research, 2019)
The bulk and surface acoustic wave velocities of Aluminum phosphide (AlP) semiconducting material under pressure up to 9.5 GPa were studied. The structural parameters and the elastic constants used in this work are taken from our previous paper published in J. Optoelec-tron. Adv. M. 16, 207 (2014). The results obtained at zero-pressure are analyzed and compared with other data of the literature. In addition, the acoustic Grüneisen parameter and the Vickers and Knoop microhardness are predicted and analyzed in detail. Our calculated results are in good agreement with the experimental and other theoretical data of literature.